The mussel larvae microbiome changes in response to a temperature rise - Zhu, You-Ting; Liang, Xiao; Liu, Tian-Tian; Power, Deborah M.; Li, Yi-Feng; Yang, Jin-Long (Frontiers in Marine Science, 2024)
Ocean warming caused by global climate change influences the function, diversity, and community dynamics of commensal microorganisms, including the hemolymph and the gut microbiota in mussels. However, the microbiota in hard-shelled mussel (Mytilus coruscus) larvae and the effect of temperature on the microbial community structure have yet to be studied. Herein, we investigated the core microbiota of M. coruscus larvae and the impact of acute (4 h) and gradual (4 days) exposure to a rise in seawater temperature from 21 to 25 ℃. Eleven core genera were identified in M. coruscus larvae by 16S rDNA gene sequencing: Alteromonas, Brevundimonas, Delftia, Microbacterium, Neptuniibacter, Neptunomonas, Pseudoalteromonas, Rhodococcus, Stenotrophomonas, Tenacibaculum, and Thalassotalea. The microbiota of larvae in the short exposure treatment was similar to the control. However, the abundance of Delftia, Neptunomonas, Pseudoalteromonadaceae, Rhodococcus, and Stenotrophomonas decreased significantly in the long-exposure larvae. In contrast, at the genus level, the abundance of Tenacibaculum increased significantly. Diversity and multivariate analyses confirmed that the microbiota patterns were linked to seawater warming over the long term. Microbiota diversity did not change significantly, regardless of whether the seawater temperature increased quickly or slowly; however, we observed a significant increase in the microbiota species abundance at higher temperatures. Among the altered bacterial genera, Delftia, Neptunomonas, and Rhodococcus function in the degradation of organic compounds; Pseudoalteromonas is closely associated with mussel attachment and metamorphosis, and Tenacibaculum is an opportunistic pathogen that can cause marine mollusk death. The results suggest that marine heat waves caused by climate change may reduce the ability of symbiotic bacteria to degrade environmental toxins, will affect mussel larvae metamorphosis, and increase the abundance of opportunistic pathogens, thereby increasing the risk of disease and death of mussel larvae.